Writing Art - Fernando, Jeremy (punctum books, 2015)
Writing Art is an attempt to respond to the possibilities of art, the potentialities in art, to the possible event that art is. Keeping in mind that events are always already potentially beyond us, are quite possibly unknown, unknowable. In this book, Jeremy Fernando meditates on art through a response to specifics works, to the specificity of the craft, tekhnē, of each work; offering a reading of specific works of photography (Photovoice sg), poetry (Tammy Ho Lai-Ming), installation art (Charles Lim), film (Tan Chui Mui), conceptual art (ZXEROKOOL), and charcoal drawings (Yanyun Chen). Through writing. For, to write is always also to scribble, to scratch, tear, quite possibly open - and perhaps more importantly, to open the possibility of a relation with another, to the unknowability that is the other. At the risk that this writing causes one to writhe, to be torn, to cry out; even if the very one is himself.